Simulasi Pengisian Air Ketel Menggunakan Rangkaian IC Gerbang Logika Dasar Sesuai di MV. Tanto Setia - Ardhi Kurniawan; Ahmad Wahyudiono; Sri Purwantini (Politeknik Ilmu Pelayaran Semarang, 2020)
Filling up water for boiler need a control system for fill up the water into the boiler. This control system using integrated circuit with the logic gates. there is some way for make the control system for boiler water fill up. This control system will be simulated using the integrated circuit that can operated by manual or auto. The purpose of this study is knowing how to make boiler water filling up simulation using integrated circuit logic gates that can operated by manual or auto like in the MV.Tanto Setia. Study methodes that we use is descriptive method for describe and explain the process of make the simulation toolsfor boiler water fill up also the theory that connect with controlling the tools. Experiments and savings are directly carried out in the process of making tool control to match what is expected. The result of this simulation using circuit IC NOR 4001 Boiler water fill up effected by water level sensor. But the sensor will not effect if the control put to manual mode. The integrated circuit more easy to understand for the beginner.